Przebieg infekcji SARS-CoV-2 u kobiet ciężarnych – przegląd literatury - Zgliczyńska, Magdalena; Kosińska-Kaczyńska, Katarzyna (Wiedza Medyczna, 2020)
The new coronavirus, severe acute respiratory syndrome virus 2 (SARS-CoV-2), causing coronavirus 2019 (COVID-19), was first identified at the end of 2019 after the series of the viral pneumonia cases in Wuhan, China. It quickly spread to other countries and continents. On March 12, 2020 the World Health Organization officially announced an outbreak of a pandemic. Patients of all ages are susceptible to SARS-CoV-2 infection, but a full-blown coronavirus disease is more common in adults, especially older men, with comorbidities. Pregnancy is a physiological condition characterized by altered immunity and hormonal balance, which are crucial, among others, for the achievement of immunological tolerance for the developing fetus. In case of some viral infections, mainly respiratory (e.g. influenza H1N1 or SARS), the population of pregnant women has been shown to be at high risk of severe course of the disease. The aim of the study was to summarize the available data on the course of SARS- -CoV-2 infection in pregnant women, its impact on pregnancy and childbirth, as well as the possibility of vertical transmission. Currently, there is no evidence of significant differences in clinical symptoms and the course of the disease between pregnant women compared and the general population of a similar age. COVID-19 in pregnant women may be associated with an increased risk of preterm delivery, premature rupture of the membranes or preeclampsia, but the available data is insufficient. There is also no conclusive evidence of the vertical transmission of the infection or its risk is low. In the light of the dynamic epidemiological situation and continuous research on SARS-CoV-2, to ensure the highest quality of care for pregnant patients, it is necessary to constantly update our knowledge in this topic.